2D Van der Waals Rare Earth Material Based Ratiometric Luminescence Thermography Integrated on Micro–Nano Devices Vertically. Issue 6 (19th February 2022) - Chen, Ping; Xu, Xiang; Li, Dongyan; Li, Zexin; Wang, Haoyun; Pi, Lejing; Zhou, Xing; Zhai, Tianyou
Abstract: Remote and real‐time thermography integrated on micro–nano devices vertically can promote the integration while estimating their operation, which is hitherto challenging. Here, the ratiometric luminescence thermography integrated on micro–nano devices vertically based on 2D van der Waals (vdW) rare earth (RE) material ErOCl is demonstrated. Ratiometric luminescence intensity varies linearly with temperature deriving from the thermal activation between two thermally coupled levels. Typically, this ratiometric micro–nano thermometer has a wide sensing range (300–700 K), high relative sensitivity (2.2% K −1 at 300 K), and high repeatability. With layered structure and insulated properties, 2D ErOCl can be easily integrated on the target chips vertically without dangling bonds so that a high‐density integration can be easily realized. Therefore, 2D ErOCl is employed for thermography of a designed micro–nano device, showing real‐time, high‐resolution temperature distribution of single device even at electrodes with different morphologies. The feasibility of this temperature sensor is further proved by COMSOL simulation. This novel approach, 2D vdW RE based ratiometric luminescence thermography, provides an excellent platform to the development of high performance eletronics with higher integration. Abstract : This work reports the ratiometric luminescence thermography integrated on micro–nano devices vertically based on 2D van der Waals rare earth material ErOCl. 2D ErOCl endows the thermometer with wide‐range temperature probing (300–700 K), high relative sensitivity (2.2% K −1 at 300 K), and high repeatability. This novel approach will shed light on the development of a higher integration of electronics.